2009
DOI: 10.1536/ihj.50.161
|View full text |Cite
|
Sign up to set email alerts
|

Development and Significance of a Fetal Electrocardiogram Recorded by Signal-Averaged High-Amplification Electrocardiography

Abstract: SummaryAlthough ultrasonic diagnostic imaging and fetal heart monitors have undergone great technological improvements, the development and use of fetal electrocardiograms to evaluate fetal arrhythmias and autonomic nervous activity have not been fully established. We verified the clinical significance of the novel signal-averaged vector-projected high amplification ECG (SAVP-ECG) method in fetuses from 48 gravidas at 32-41 weeks of gestation and in 34 neonates. SAVP-ECGs from fetuses and newborns were recorde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 26 publications
1
14
0
Order By: Relevance
“…Development of the sympathetic nerves begins around the 20th gestational week, later than does that of the parasympathetic nerves, and is most rapid during the 26th to 30th gestational weeks, which coincide with the period of rapid increase in the LF power [1]. Another study [19] reported that LF/HF ratio was enhanced at 32 weeks or later, which was consistent with previous report [20] of a conversion point at 32 weeks of gestation. These neural control mechanisms will nearly reach the neonatal level in the 37th gestational week.…”
Section: Gradual Increase In Sympathetic Activity With Foetal Cardiovsupporting
confidence: 87%
“…Development of the sympathetic nerves begins around the 20th gestational week, later than does that of the parasympathetic nerves, and is most rapid during the 26th to 30th gestational weeks, which coincide with the period of rapid increase in the LF power [1]. Another study [19] reported that LF/HF ratio was enhanced at 32 weeks or later, which was consistent with previous report [20] of a conversion point at 32 weeks of gestation. These neural control mechanisms will nearly reach the neonatal level in the 37th gestational week.…”
Section: Gradual Increase In Sympathetic Activity With Foetal Cardiovsupporting
confidence: 87%
“…100 mV) with a low signal-to-noise ratio, and so the T wave of the fECG can only be detected consistently from about 15 weeks. Figure 6 collects data from the literature on the period of the human foetal heartbeat, obtained from ultrasonography [23,24], and RR intervals and QT intervals, obtained from fECG [25,26] or foetal magnetocardiographic recordings [27]. The period and RR intervals (represented by black squares in figure 6) decrease from approximately 640 ms (at four weeks) to a minimum of 350 ms (at eight weeks) and then drift upward to around 400 ms for the remaining period of gestation.…”
Section: Rsfsroyalsocietypublishingorg Interface Focus 3: 20120065mentioning
confidence: 99%
“…In addition, analysis of sympathetic nerve activity and depolarization and repolarization abnormalities is possible from the same recording, and the DREAM-ECG system can be used to record fetal ECG. 24) In the future, we would like to see DREAM-ECG used for maternal and perinatal screening of ECG abnormalities such as prolongation QT syndrome of the fetus and myocardial damage in pregnant women.…”
Section: Discussionmentioning
confidence: 99%